Challenges of coronavirus disease 2019 (COVID-19) in Lebanon in the midst of the economic collapse - Nada K. Zahreddine; Sara F. Haddad; Anthony Kerbage; Souha S. Kanj (Cambridge University Press, 2022)
Lebanon, one of the smallest countries in the Middle East, has held for decades a reputation for being the premier medical hub for patients from the Arab world as well as neighboring countries and for offering world-class treatment and advanced medical services. However, this once world-renowned healthcare sector is now facing a risk of imminent collapse as overlapping crises have struck the country since October 2019. In this article, we describe the concomitant political, economic, and financial challenges that Lebanon is facing, which have strained the national healthcare system and have undermined its ability to respond to the coronavirus disease 2019 (COVID-19) pandemic. We present an overview of the political instability, the Lebanese revolution with countrywide protests, as well as the devaluation of the Lebanese currency representing one of the worst economic meltdowns since the 19th century. We describe the unprecedented energy crisis the country is facing and the disastrous consequences of the Beirut port explosion of August 2020. We review the efforts and measures taken by different stakeholders to contain the COVID-19 pandemic amid the multifaceted challenges and the large exodus of healthcare personnel.